2014
DOI: 10.1111/cge.12526
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel founder MSH6 mutation causing Lynch syndrome in the French Canadian population

Abstract: We identified an MSH6 mutation (c.10C>T, p.Gln4*) causing Lynch syndrome (LS) in 11 French Canadian (FC) families from the Canadian province of Quebec. We aimed to investigate the molecular and clinical implications of this mutation among FC carriers and to assess its putative founder origin. We studied 11 probands and 27 family members. Additionally 6433 newborns, 187 colorectal cancer (CRC) cases, 381 endometrial cancer (EC) cases and 179 additional controls, all of them from Quebec, were used. Found in appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Further analysis of other members of our cancer family showed only one of five other carriers was affected by BC (unpublished data). This case is from the French Canadian population and carries a pathogenic variant in BRCA2 c.8537_8538delAG; p.Glu2846GlyfsTer22 known to be a founder pathogenic variant as reported by our group and others [84][85][86][87][88][89][90][91][92][93].…”
Section: Carriers Of a Bard1 Variant And A Pathogenic Variant In A Knsupporting
confidence: 52%
“…Further analysis of other members of our cancer family showed only one of five other carriers was affected by BC (unpublished data). This case is from the French Canadian population and carries a pathogenic variant in BRCA2 c.8537_8538delAG; p.Glu2846GlyfsTer22 known to be a founder pathogenic variant as reported by our group and others [84][85][86][87][88][89][90][91][92][93].…”
Section: Carriers Of a Bard1 Variant And A Pathogenic Variant In A Knsupporting
confidence: 52%
“…By contrast, we found that endometrioid ovarian cancer was strongly associated with endometrial cancer in the two-way comparison, which could imply association with HNPCC syndrome related to MSH6 mutations in patients with the endometrioid and clear cell ovarian carcinomas 25 . Carriers with MSH6 germline mutations appear to have a high risk of endometrial cancer but low risk of colorectal cancer 26 .…”
Section: Discussionmentioning
confidence: 99%
“…(0.092%; 1:1087), and PMS2 p.P246Cfs*3 (0.234%; 1:427) . Other research has demonstrated that the MSH6 p.Q4* founder mutation is particularly prevalent in French Canadian individuals, with an estimated carrier frequency of 0.249% (1:402), and haplotype analysis suggests that the mutation arose in a common ancestor from 430 to 656 years ago . Although their population prevalence is not well understood, founder mutations in MSH2 (c.1906G>C, p.A636P) and MSH6 (c.3959_3962delCAAG and c.3984_3987dupGTCA) appear to account for the majority of Lynch syndrome cases in individuals of Ashkenazi Jewish ancestry .…”
Section: Epidemiology Of Lynch Syndromementioning
confidence: 99%